Identification of nodes as legible features in the historical district of Kuala Lumpur, Malaysia - Ujang, Norsidah; Tan, Lai Kum (American-Eurasian Network for Scientific Information, 2014)
In the developing cities, there is an increasing concern on the causal factors of poor quality public spaces and places. Despite efforts to improve the physical and experiential qualities, it is evident that historic cities are affected by the development progress. One such a situation is the uncontrolled and unfit developments that continue to restructure the city pattern and the image of the historic district of Kuala Lumpur. That makes the historical places incoherent, therefore, illegible to the pedestrians. One of the elements that affect how people structure a city in their mental cognition is a node. Node as a space that encourages people to stop, inhabit and participate with city life. They describe places in their physical structure, activity, ambience and historical significance. This study aims to examine the legibility of nodes in the historic district of Kuala Lumpur, Malaysia. Direct observations of the historical district were carried out to examine the characteristics of the historical district and the constituting elements. Mental mapping and questionnaire survey were conducted to elicit the people's identification of nodes considered to be legible and support their experience of the district. The findings reveal that public buildings such as Masjid Jamek, transport node including Light Rail Transit (LRT) Station, the pedestrian mall next to Central Market and public open space in front of Hong Kong and Shanghai Bank (HSBC) headquarter as strategic nodes within the district. Respondents associated the nodes with paths and landmarks that directly link with the nodes. The scale and facade treatment of historical buildings defining the nodes influence the respondent's recognition of the elements. The types of activities and the intensity of people within and around the nodes encourage engagement and association with the areas. The findings suggest that the historical elements contribute to the legibility of places. In this regards, planners and urban designer should consider the potential of these elements in making the city more attractive and identifiable to users.